From Imitation to Open Innovation: A Lesson and Roadmap for China Hi-tech Intensive Industry - Sun, Shangtong (2007)
Innovation is a core business necessity, as it is known to all. Companies that do not innovate will be washed out in increasingly intensive competition nowadays. In a world of knowledge economy, companies can no longer afford to count completely on their own internal R&D efforts to create an approach of internally commercialized new products and services, but should instead take advantage of external sources of technology and innovation to promote internal growth. This is one of the main ideas of Open Innovation. In the wake of its entry into the World Trade Organization (WTO), China has made the first step to globalize its economy and benchmark with the leading markets in developed world by following the rules and practices of the global marketplace. In this background, it is crucial to introduce Open Innovation to China, and the significance will benefit Chinese companies finding their most proper business model, thereby, gaining the core competency and success. This dissertation is aiming at understanding the essentials of Open Innovation and its cooperative open business model, and examining the significance of Open Innovation to China. Based on the comparison of innovation leader countries - Japan and the U.S. and case studies which examine the practice of Chinese high-tech companies under the framework of Open Innovation, this paper generates a roadmap for Chinese companies to catch up with the fast footsteps of world-class organizations, and guilds them getting rid of imitation or Closed Innovation paradigm and going to Open Innovation paradigm